Phytochemical screening and GC-MS analysis of local durian (Durio zibethinus) leaf extract from Criwik, Rembang, Central Java, Indonesia - ANDINI DESI SAWITRI; ENDANG YUNIASTUTI; EDI PURWANTO; PARJANTO PARJANTO (Society for Indonesian Biodiversity, 2025)
Abstract. Sawitri AD, Yuniastuti E, Purwanto E, Parjanto. 2025. Phytochemical screening and GC-MS analysis of local durian (Durio zibethinus) leaf extract from Criwik, Rembang, Central Java, Indonesia. Biodiversitas 26: 55-61. Durian (Durio zibethinus), an important tropical fruit in Indonesia, is widely known for its unique flavor and potential health benefits. Despite extensive research on the nutritional and pharmacological properties of its fruit, the bioactive potential of its other plant parts, particularly the leaves, remains limited. This study explored the phytochemical profile and bioactive compounds in the leaf extract of Criwik durian, a local variety from Rembang, Central Java, Indonesia. Phytochemical screening confirmed the presence of flavonoids, tannins, alkaloids, saponins, and phenolic compounds, all known for their diverse pharmacological activities, including antioxidant, anti-inflammatory, and antimicrobial properties. Importantly, this is the first study to report the presence of phytochemical in the durian leaf extract. Additionally, gas chromatography-mass spectrometry analysis was conducted to characterize the bioactive components, which identified 11 distinct compounds. These included squalene, ethyl iso allocholate, neophytadiene, and phytol, all associated with health remedies and pharmacological effects. These results provide a detailed chemical profile of Criwik durian leaves, highlighting their potential as a valuable resource for the development of natural health products and herbal remedies. These findings enhance our understanding of the bioactive potential of durian leaves and encourage further research into their medicinal applications. Thus, Criwik durian leaves could serve as a promising source for the future exploration of natural health product development and sustainable medicinal practices.